HOW ENGAGEMENT, SELF-EFFICACY, AND ENVIRONMENT AFFECT BANK EMPLOYEE PERFORMANCE - Nurillah, Vina Riza; Winahyu, Pawestri; Murtaliningtyas, Wenny (Univesitas Muhammadiyah Tangerang, 2025)
Human resources are an important element in supporting the smooth operation of an organization. Improving the quality and acquisition of the company is determined by the employees in which employee performance is the main benchmark for the success of the organization, the goal of the organization always strives to improve employee performance so that the company is able to achieve its vision and mission. This study aims to find out and analyze the role of employee engagement, self-efficacy and work environment variables on employee performance in Kb Bank Jember. This type of research uses a quantitative method with a sample of 33 employees at Kb Bank Jember and uses a Nonprobability sampling technique with a saturated sampling technique using a data collection technique in the form of a questionnaire to respondents. The data analysis technique of this study uses instrument testing, classical assumptions, multiple linear regression, hypotheses and determination coefficients. The results of the analysis obtained showed that employee engagement, self efficacy and work environment had a positive and significant effect partially on the performance of Kb Bank Jember employees, and the results of the R2 Detremination Coefficient test obtained an influence contribution rate of 87%.